# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \frac {6 x^{2}+4}{3 y^{2}-4 y}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (y^{2}-1\right ) y^{\prime } = 4 x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-y}+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2+\sqrt {x}}{2+\sqrt {y}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 x^{2} y^{2} = -3 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 x^{2} y^{2} = 3 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 200 y-2 y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = -10
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x -1+2 x y-y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y^{2}-y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y^{2}-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}-1}{x y}
\] |
✓ |
✓ |
|
\[
{}\left (y^{2}-1\right ) y^{\prime } = 4 x y
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+3 x^{2} y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } y^{2}+3 x^{2} y = \sin \left (x \right )
\] |
✗ |
✗ |
|
\[
{}y^{\prime }-x y^{2} = \sqrt {x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+\left (x y+3 y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x y+3 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 y+8
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-{\mathrm e}^{2 x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y = y^{3}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\cos \left (x^{2}\right ) = 827 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 6
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 20 \,{\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 y+16 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+3 y-10 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {x}+3 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \cos \left (x \right )+y \sin \left (x \right ) = \cos \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\left (5 x +2\right ) y = \frac {20}{x}
\] |
✓ |
✓ |
|
\[
{}2 \sqrt {x}\, y^{\prime }+y = 2 x \,{\mathrm e}^{-\sqrt {x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 y = 6
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 y = 6
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+5 y = {\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}3 y+x y^{\prime } = 20 x^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+x^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = x \left (3+3 x^{2}-y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+6 x y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+x y = \sqrt {x}\, \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x^{2} {\mathrm e}^{-x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{\left (3 x +3 y+2\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (3 x -2 y\right )^{2}+1}{3 x -2 y}+\frac {3}{2}
\] |
✓ |
✓ |
|
\[
{}\cos \left (-4 y+8 x -3\right ) y^{\prime } = 2+2 \cos \left (-4 y+8 x -3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+\left (y-x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-x y = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}+\frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}\cos \left (\frac {y}{x}\right ) \left (y^{\prime }-\frac {y}{x}\right ) = 1+\sin \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x -y}{x +y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = 3 y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {3 y}{x} = \frac {y^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y \cot \left (x \right ) = 6 \cos \left (x \right ) y^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{x} = \frac {1}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}+\frac {x^{2}}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime } = -2+\sqrt {2 x +3 y+4}
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime }+\frac {2 y}{x} = 4 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4+\frac {1}{\sin \left (4 x -y\right )}
\] |
✓ |
✓ |
|
\[
{}\left (y-x \right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}\left (2 x y+2 x^{2}\right ) y^{\prime } = x^{2}+2 x y+2 y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = x^{2} y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \sqrt {2 x +y-3}-2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \sqrt {2 x +y-3}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = \sqrt {x y+x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = \frac {28 \,{\mathrm e}^{2 x}}{y^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x -y+3\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x = 2 \sqrt {x^{2}+y}
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right ) y^{\prime } = {\mathrm e}^{-x}-\sin \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \left (1+\frac {2 y}{x^{2}}+\frac {y^{2}}{x^{4}}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{y}-\frac {y}{2 x}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x y^{2}-x^{2}} \left (y^{2}-2 x \right )+2 \,{\mathrm e}^{x y^{2}-x^{2}} x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y+y^{2}+\left (2 x y+x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{3}+4 x^{3}+3 y^{2} y^{\prime } x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}2-2 x +3 y^{\prime } y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}1+3 x^{2} y^{2}+\left (2 x^{3} y+6 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{3} y+\left (x^{4}-y^{4}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+\ln \left (x y\right )+\frac {x y^{\prime }}{y} = 0
\] |
✓ |
✓ |
|
\[
{}1+{\mathrm e}^{y}+x \,{\mathrm e}^{y} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y}+\left (x \,{\mathrm e}^{y}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+y^{4}+x y^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+\left (y^{4}-3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {2 y}{x}+\left (4 x^{2} y-3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+\left (1-x \tan \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y+3 y^{2}+\left (2 x +4 x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x \left (1+y\right )-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{3}+\left (4 x^{3} y^{3}-3 x y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 x y+\left (3 x^{2}+5 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}6+12 x^{2} y^{2}+\left (7 x^{3} y+\frac {x}{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 y-6 x^{3}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 y^{2}-6 y
\] |
✓ |
✓ |
|
\[
{}4 y^{2}-x^{2} y^{2}+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {x +y}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-\sqrt {x} = 3
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime }-y^{2} = \sqrt {x^{2} y^{2}+x^{4}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-2 x y+x^{2}
\] |
✓ |
✓ |
|